A Hollow Porous CdS Photocatalyst. Issue 45 (25th September 2018) - Sun, Qiming; Wang, Ning; Yu, Jihong; Yu, Jimmy C.
Abstract: Efficient light harvesting and charge separation are of great importance in solar‐energy conversion on photocatalysts. Herein, the synthesis of a novel hollow porous CdS photocatalyst with effectively restrained electron–hole recombination is reported. By using microporous zeolites as a host and a hard template, ultrasmall Pd and PdS nanoparticles can be anchored separately onto the inner and outer surfaces of a hollow CdS structure. The metallic Pd pulls the photoexcited electrons away from CdS while PdS pushes the holes for more thorough oxidation of the sacrificial agent. The final Pd@CdS/PdS product exhibits superior visible‐light‐driven photocatalytic H2 evolution rate of up to 144.8 mmol h −1 g −1 . This is among the highest values of all the reported CdS‐based catalysts. This synthetic approach may be used to fabricate other highly efficient catalysts with spatially separated cocatalysts. Abstract : Hollow porous CdS with spatially separated Pd and PdS cocatalysts is synthesized by a versatile approach using microporous zeolites as the hosts and templates. The charge recombination can be greatly suppressed by the push and pull actions of the cocatalysts. The Pd@CdS/PdS product exhibits an impressive photocatalytic H2 evolution rate of 144.8 mmol h −1 g −1 .